On the Post-embryonic Development of the Female Reproductive Organs of Tribolium castaneum Herbst with a Note on the Homology of the Reproductive Organs in the two Sexes (Coleoptera: Tenebrionidae). - Srivastava, Uma Shanker (Contributions to Entomology = Beiträge zur Entomologie, 1956)
The entire efferent system of Tribolium originally develops from two invaginations - the primary genital invagination or spermathecal rudiment formed on the posterior border of the ninth sternite in the larval stage and the uterine rudiment formed on the eighth sternite in the pupal stage. As the two invaginations develop, they form two tubes running one upon the other. Later, their median parts come in close contact with each other, the walls of the spermathecal rudiment go down to embrace the uterine rudiment and finally, the two become confluent, their anterior and posterior parts remaining distinct. Meanwhile, the anterior part of the spermathecal rudiment divides by a horizontal cleft into a dorsal part which gives rise to the spermathecal gland and a ventral part which gives rise to the spermatheca and the bursa; the anterior end of the uterine rudiment divides to form the lateral oviducts which joins with the mesodermal lateral oviducts. The posterior part of the uterine rudiment now disappears so that a single pore on the ninth segment is left. The ovipositor arises from a pair of rudiments on the sides of the primary genital invagination. Later these differentiate into the coxites and styli.